KONSTRUKSI EPISTEMOLOGIS PENALARAN HUKUM IMAM SYÂFI’Î Asep Opik Akbar - Asep Opik Akbar (AHKAM : Jurnal Ilmu Syariah, 2014)
Epistemological Construction of Imam Syâfi’î Legal Reasoning. Imam Syâfi’î has a major contribution in laying the foundation and methodological principles of Islamic law (ushûl al-fiqh), supporting a strong unity between the Alquran and the Sunah as well as providing a level of convergence between the reasoning of ahl al-hadîtsand ahl al-ra’y. The methodology offered by Imam Syâfi’î is well suited and relevant to the context of the social and cultural conditions of the time. This article elaborates more comprehensively on the legal reasoning offered by the Imam Syâfi’î. However, in the current context, the process of legal reasoning that is offered by Imam Syâfi’î deserves further study considering the different challenges and opportunities. Other ijtihâdmethods need to be considered in the legal process at this time.DOI: 10.15408/ajis.v14i2.1277